News Briefs (Gifted child today magazine, 2017)
Notable The American Psychological Foundation recently announced the recipients of the 2017 Esther Katz Rosen Fund Grants: Dr. Mija Van Der Wege, Carleton College, received US$25,000 for her project, “Summer Psychology Connections at Carleton College, Phase II,” and Dr. Matthew Makel, Duke University, received US$45,000 for his proposal, “Calculating Characteristics in Gifted Students.” The following states, universities, and public schools were awarded grants by the Jacob K. Javits Gifted and Talented Students Education Program for 2015-2016: From these participants, they found 20% of the total school age population is enrolled in a foreign language, 11 states have foreign language graduation requirements, 16 states do not have foreign language graduation requirements, and 24 states have graduation requirements that may be fulfilled by a number of subjects—one being foreign languages.